The Significance of Ideological and Political Education in College Physical Education - Fu, Kexin (Journal of Theory and Practice of Social Science, 2023)
Physical education is an indispensable part of the ideological and political education in Colleges and universities, and it is a course to promote the all-round development of students' morality, intelligence, physique, and beauty. By Integrating Ideological and political education into various sports activities, college students can develop excellent ideological and moral character. But at present, there are still some colleges and universities of physical education is still in the exam oriented teaching state, or there are some deficiencies, can not help college students to shape the correct outlook on the person and values, this paper also puts forward some suggestions; the following is the ideological and political education function of College physical education. Document, picture, and audio are static teaching content display in micro course, which can let students receive knowledge directly. For example, in the construction of document resources, designers need to highlight the content theme, and use color to distinguish the key points in the document, which can not only help students quickly obtain important content, but also change the boring long text. The picture resources are relatively simple, only need to be modified and processed by PS and other image processing software. Finally, audio resources mainly use text or pictures to prompt the content. This kind of audio resources can be directly produced through mobile phones. At present, there are many ways to make audio resources by using mobile phones.